2014
DOI: 10.23953/cloud.ijanhs.152
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 Intake Correlated to Physical and Mental Improvements in Multiple Sclerosis Specific Quality of Life

Abstract: Current literature fails to provide individuals with multiple sclerosis (MS) specific dietary recommendations to advance quality of life (QOL). Due to the important structural and functional roles of vitamin B 12 in the nervous system, the purpose of this research was to determine possible correlations between dietary intake of vitamin B 12 and self-reported quality of life (QOL) among individuals with MS. The National MS Society and MS Foundation were used to recruit volunteers age 18 and older with a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…The effect of debilitating chronic diseases such as MS and their attendant problems, including the impact of disability on quality of life in all dimensions is obvious [22]. Increasing the consumption of folic acid and vitamin B12 improved physical and mental dimensions of quality of life which is in line with the findings of our study [23]. Zhang et al [24] have shown that vitamin B12 can reduce pain in some neurological diseases such as MS.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The effect of debilitating chronic diseases such as MS and their attendant problems, including the impact of disability on quality of life in all dimensions is obvious [22]. Increasing the consumption of folic acid and vitamin B12 improved physical and mental dimensions of quality of life which is in line with the findings of our study [23]. Zhang et al [24] have shown that vitamin B12 can reduce pain in some neurological diseases such as MS.…”
Section: Discussionsupporting
confidence: 87%
“…This effect was also seen in the vitamin group of the present study. Pietro et al [23] studied on 2 groups of patients with MS and reported that the group of subjects who consumed more than 4.2 µg of vitamin B12 on daily bases had a greater improvement in the quality of life compared to the group that consumed less than 4.2 µg of this vitamin per day. The results of the present study indicated that vitamin B12 and folic acid consumption significantly improved both physical and mental dimensions of life quality in the vitamin group; but in the placebo group, improvements were only limited to the psychological dimension of quality of life and no significant change in the physical dimension was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with HGI carbohydrate consumption, in contrast with participants in low GI categories, had lower intake of vitamin B12, vitamin D, and biotin, where these nutrients have been reported to positively effect the nervous system, and neurotransmitter transportation and synthesis [12][13][14]. Studies have shown that increases in the intake of vitamin B12 led to an improvement in QOL measures, which can be referred to emotional well-being [41]. Therefore the role of B12 in the RE can justify our results; across the GI categories, the RE has decreasing trends.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] Pietro et al ., 2014 as well, showed in a study about the effect of B12 Vitamin's use on the patients with MS that the aspect of quality of life (physical and psychological) have been more improved in the individuals who took this vitamin for 2.4 mg everyday. [ 36 ] Ryan-Harshman and Aldoori, 2008showed that the use of B12 vitamin leads to an increase in the quality of life in the individuals with nervous problems. [ 37 ] In the study by Moghadam et al .…”
Section: Discussionmentioning
confidence: 99%